W/AlSiTiNx/SiAlTiOyNx/SiAlOx multilayered solar thermal selective absorber coating. (1st September 2020) - AL-Rjoub, A.; Rebouta, L.; Cunha, N.F.; Fernandes, F.; Barradas, N.P.; Alves, E.
Highlights: Solar selective absorber design for high temperature applications. High stability and good oxidation resistance of solar thermal optical stack. Improved selective solar thermal absorber based on AlSiTiNx and SiAlTiOy Nx . Abstract: Solar thermal energy has often been used as a renewable green energy source. Here we present a design composed of a highly selective solar thermal absorber coating that has been deposited by DC magnetron sputtering. This will consist of four layers: W/AlSiTiNx /SiAlTiOy Nx /SiAlOx . The coating that was utilised revealed an excellent average solar thermal absorbance, (α = 95.5%) with very low emittance, (ε = 9.6% calculated for 500 °C) together with an excellent thermal stability after annealed at 500 °C, in air for 350 h, and at 630 °C in vacuum for 220 h.